THE EFFECT OF THE PROJECT BASED LEARNING MODEL ON IMPROVING THE COMPETENCE OF PRACTICAL LEARNING OF VOCATIONAL STUDENTS: A REVIEW - Dewangga, Andrian Wisnu; Ahmad, Noesanto Dewantoro (Department of Mechanical Engineering Education, 2023)
This research aims to evaluate the effect of implementing the Project Based Learning (PjBL) Model on increasing the practical learning competence of Vocational High School students. Data collection was carried out through a literature review. This research is a literature review research that adopts a narrative review type, which aims to comprehensively investigate and analyze various scientific articles related to the research topic. Identify relevant literature, researchers conducted a search using the keyword